HASIL TANAMAN KUBIS BUNGA (Brassica oleracea var. botrytis L.) PADA JARAK TANAM DAN MULSA ORGANIK - Hafidha Ade Luthfiana; Gembong Haryono; Historiawati Historiawati (Universitas Tidar, 2019)
The research about the yield of cauliflower (Brassica olerace var. botrytis, L.) on plant spacing and organic mulching. The research was conducted from April to July 2018 at Banyuwangi Village, Bandongan District, Magelang Regency with altitude 400 m asl, soil type regosol with a pH 5,8 – 6,0. The purpose of the research to determine the plant spacing and suitable organic mulching on yield of cauliflower. The research type (3 x2) factorial experiment arranged in randomized completed, block design repeated four times. The first factor was plant spacing: 50 cm x 40 cm (J1), 50 cm x 50 cm (J2) and 50 cm x 60 cm (J3). The second factor was organic mulching: straw mulch (M1) and bamboo leaf litter mulch (M2). The result of the research showed that increase in the population of cauliflower plants increase the height of plants and the fresh weight of flowers per square meter but decreases the number of leaves, diameter cauliflower and fresh weight of cauliflower per plant. Provision of bamboo leaf litter mulch increases plant height and fresh weight of cauliflower per plant while straw mulch increases the specific weight of cauliflower. Increased population of cauliflower plants with straw mulch decreasing the specific weight of cauliflower but an increasing in population of cauliflower plants with mulch leaves and bamboo leaves litter mulch increasing the specific weight of cauliflowers.